Open Parliament: Study from Indonesia and Philippines - Afandi, Syed Agung; Erdayani, Rizki; Afandi, Muslim (Department of Government Studies, Universitas Syiah Kuala, 2024)
This research aims to analyze the trend of open parliaments in Indonesia and the Philippines and the commitment of the parliaments of the two countries. This research uses a qualitative approach with bibliometric analysis and content analysis methods. The results of this research show that the Indonesian open parliament study has a higher number of publications, citations, h-index, and g-index, so that it has a greater impact and productivity. Even though Indonesian open parliament articles have higher total link strength and occurrences, the Philippine open parliament study is more focused on certain topics. There are more themes and clusters in the Indonesian open parliament study, and each cluster describes the relationship between certain themes and focuses. Network visualization, overlay visualization, and density visualization generate potential research themes regarding this study in the future. Even though the Indonesian and Philippine parliaments have stated their commitment to support open parliaments in both countries, the Indonesian parliament's commitment has a stronger influence through the formation of an open parliament institution.